2016
DOI: 10.3109/10717544.2016.1172368
|View full text |Cite
|
Sign up to set email alerts
|

In vivo tissue distribution and efficacy studies for cyclosporin A loaded nano-decorated subconjunctival implants

Abstract: Biodegradable implants are promising drug delivery systems for sustained release ocular drug delivery with the benefits such as minimum systemic side effects, constant drug concentration at the target site and getting cleared without surgical removal. Dry eye syndrome (DES) is a common disease characterized with the changes in ocular epithelia surface and results in inflammatory reaction that might lead to blindness. Cyclosporin A (CsA) is a cyclic peptide that is frequently employed for the treatment of DES a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…Parallel copper electrodes in 1.8 cm distance from each other were used as a collector. In order to obtain PU nanofibers with aligned and smooth morphology, we optimized the electrospinning parameters such as polymer concentration, the distance between needle and collector, applied voltage and flow rate . Electrospinning solution was prepared by dissolving PU in tetrahidrofurano/dimethylformamide (60:40 [v/v]) solvent mixture and making 8% (w/v) concentration of PU.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Parallel copper electrodes in 1.8 cm distance from each other were used as a collector. In order to obtain PU nanofibers with aligned and smooth morphology, we optimized the electrospinning parameters such as polymer concentration, the distance between needle and collector, applied voltage and flow rate . Electrospinning solution was prepared by dissolving PU in tetrahidrofurano/dimethylformamide (60:40 [v/v]) solvent mixture and making 8% (w/v) concentration of PU.…”
Section: Methodsmentioning
confidence: 99%
“…In order to obtain PU nanofibers with aligned and smooth morphology, we optimized the electrospinning parameters such as polymer concentration, the distance between needle and collector, applied voltage and flow rate. [22][23][24][25][26][27] Electrospinning solution was prepared by dissolving PU in tetrahidrofurano/dimethylformamide (60:40 [v/v]) solvent mixture and making 8% (w/v) concentration of PU. Polymer solutions were placed in a glass syringe (5 mL) bearing metallic capillary (0.41 mm i.d.)…”
Section: Preparation Of Aligned Pu Nanofiber Scaffoldsmentioning
confidence: 99%
“…In vivo ocular irritation studies using the Draize test on New Zealand white albino rabbits demonstrated that the meloxicam nanocrystals-laden contact lenses were significantly less irritating to the ocular tissues when compared with the marketed drug solution alone [225]. Yavuz et al prepared CsA-loaded PLGA 85:15 or PCL (MW 30,000–70,000 Da) nanoparticles by o/w emulsification solvent evaporation technique and then incorporated the nanoparticles into PCL implant/fiber composite system by electrospinning/implant molding method [232]. They found that CsA was present in cornea, sclera and lens even 90 days after subconjunctival implantation of the composite systems in dry-eye induced mice.…”
Section: Nanoparticles For Drug Delivery To the Anterior Segmentmentioning
confidence: 99%
“…They found that CsA was present in cornea, sclera and lens even 90 days after subconjunctival implantation of the composite systems in dry-eye induced mice. The fiber composite system had better CsA tissue concentration and healing process than the implant composite system [232]. Yang et.…”
Section: Nanoparticles For Drug Delivery To the Anterior Segmentmentioning
confidence: 99%
“…They are particularly important in cancer therapy where the therapeutic index of the drug is often quite small and the stability of biologic agents is limited. 24, 40 In situ forming implants (ISFI) used for local drug delivery directly into the tissue of interest (e.g. a tumor) are an attractive alternative route to oral and intravenous administration.…”
Section: Introductionmentioning
confidence: 99%